Intensity of Instagram use, social comparison and self-esteem among public university students in Klang Valley - Mohamed Johar, Nurul Hidayah; Hasbullah, Muslihah (Human Resources Management Academic Research Society (HRMARS), 2024)
Social media usage has ingrained itself into modern society. Some are concerned about how social media's high exposure, especially the usage of Instagram by young adults, may impact their subjective well-being. Instagram allows users to assess themselves through social comparisons with other users, which puts their self-esteem at risk. For university students to avoid psychological issues and reach their full potential throughout life, they must have a positive outlook on self-esteem. This study aimed to determine the relationship between intensity of Instagram use, social comparison and self-esteem among public university students in Klang Valley. A total of 220 students has participated and they were chosen by using a multi-stage cluster random sampling technique. The data was collected through a self-administered questionnaire. Measurements used were an Instagram Intensity Scale (Stapleton, Luiz, & Chatwin, 2017) to measure the Instagram intensity, Iowa-Netherlands Comparison Orientation Measure (Gibbons & Buunk, 1999) to measure social comparison and Rosenberg Self-Esteem Scale (Rosenberg, 1965) to measure self-esteem. Findings demonstrated that intensity of Instagram and self-esteem were significantly negatively correlated (r=-0.20, p< 0.01), also between the ability comparison and self-esteem (r=-0.36, p< 0.01). Besides, a significant positive correlation was found between opinion comparison and self-esteem (r=0.39, p< 0.01). This study concluded that ability comparison and opinion comparison were significant predictors for self-esteem among the respondents. Thus, reducing ability comparison and encouraging opinion comparison are essential to foster students’ self-esteem. The findings could pave the way for the university to address the issue of students’ self-esteem comprehensively. Universities should focus on intervention programs that promote self-love to increase self-esteem and to increase awareness of social media addiction to protect mental health of young adults. Future research may explore on the influence of cultural sensitivity and gender differences towards self-esteem and social comparison among young adults.